Counseling on Clean and Healthy Behavior (PHBS) in MTsN 1 Lebak - Achmad Machron Chairulfalah; Lia Nurliana; Nurjaman Nurjaman; Trikawati Trikawati (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
Clean and Healthy Behavior, or PHBS, is crucial and should be practiced on a daily basis.The Clean and Healthy Behavior (PHBS) program is one way to make unhealthy behavior healthy because it is caused by behavioral factors that contribute between 30 and 35 percent to health.One of the reasons is that students aren't aware of how to practice healthy habits like putting trash where it belongs, washing their hands before eating, and keeping the classroom clean.The only way that clean and healthy living behaviors are promoted is through an appeal to change behavior.For instance, the school will enact rules that prohibit littering if students are encouraged to place garbage where it belongs.If students are not made more aware of the importance of living a clean and healthy lifestyle, these appeals and regulations will not be effective.As a result, more information about the significance of maintaining a clean and healthy lifestyle in the school setting is required.In order for students to independently prevent disease, improve their health, and actively contribute to the creation of a healthy environment, all of the behaviors they engage in in the school setting are informed by their education.